Sports and ethnicism: Instruments of labour control at the Messina Copper Mines, 1920-1960 (Historia, 2021)
The article attempts to investigate the type of recreational and competitive sports which were introduced by the Messina mine management, who were British by origin, to the African communities of Messina, Harper, Campbell and Artonvilla compounds. Attention is focused on how the working class in the process of their sports activities displayed signs of conflict and division due to ethnic and regional affiliations especially in competitive sports.
Keywords: African Fist Fighting; Messina copper mines; Musango, Athletics; Apartheid politics; Recreational activities; Gender discrimination; History; Recreation; Segregation sports policies; Soccer; Skittles; Sport; Tennis